Cilostazol for Chinese Patients with Aspirin Intolerance after Coronary Drug-Eluting Stent Implantation - Dai, Chunfeng; Chen, Zhangwei; Fu, Jiayu; Qian, Juying; Ge, Junbo (Thrombosis and Haemostasis, 2020)
Background Cilostazol-based dual antiplatelet therapy (DAPT) is widely used in patients with aspirin intolerance after coronary drug-eluting stent (DES) implantation in China. However, this empirical strategy is not recommended or even mentioned in Chinese or international guidelines due to a lack of evidence from large-scale studies. We aimed to explore the efficacy and safety of cilostazol-based DAPT in this special population.Methods In this cohort study, patients were grouped according to the DAPT strategy that they received after coronary DES implantation. The primary efficacy endpoint was major adverse cardiovascular and cerebrovascular events (MACCEs). Angiographic follow-up and major bleeding events were also recorded.Results A total of 918 patients receiving cilostazol-based DAPT due to aspirin intolerance were enrolled, matched with 918 patients receiving aspirin-based DAPT. After 15-month prospective follow-up, the cilostazol group had lower risk of MACCE (5.1% vs. 7.6%, propensity score adjusted hazard ratio = 0.671 [95% confidence interval 0.462–0.974], p = 0.036) compared with the aspirin group. Lower rate of coronary lesion progression was also found through follow-up angiography in the cilostazol group (17.4% vs. 23.6%, p = 0.022), especially in nontarget lesions (12.1% vs. 17.6%, p = 0.019). The two groups had the same risk of major bleeding events (0.8% vs. 0.4%, p = 0.364).Conclusion In the current study, cilostazol is a good substitute for aspirin in patients who have aspirin intolerance but need DAPT after coronary DES implantation in China. However, large-scale randomized controlled trials were still required to further confirm its efficacy and safety.
Keywords: cilostazol; aspirin intolerance; cohort study; coronary artery disease